Caring for a family member or friend with dementia at the end of life: A scoping review and implications for palliative care practice. (March 2018) - Broady, Timothy R; Saich, Freya; Hinton, Tom
Background: Although people with dementia receive substantial care from informal sources, there is limited research available that investigates how these carers experience end-of-life care. Aim: This review aimed to identify what is currently known about carers' experiences of providing end-of-life care to a family member or friend with dementia and draw implications for palliative care policy and service provision. Design: A scoping literature review was conducted, first using a targeted key word search, followed by assessments of eligibility based on title and then abstract content. Data sources: Records were sourced through PsycINFO, PubMed and CINAHL databases. Peer-reviewed papers published between 2000 and 2016, reporting on data collected directly from carers, were included for review. Results: Carers' experience centred on relationships (with care recipients, family and friends and health care professionals) and the specific context of caring for someone with dementia. These broad categories of carers' experiences had clear influences on them personally, particularly in relation to their sense of self and their wellbeing. Conclusion: Palliative care services would benefit from ensuring holistic approaches to supporting people with dementia, their carers and wider family networks. Tailoring services to the specific context of dementia would enable effective, personalised support throughout extended periods leading up to care recipient death as well as through the challenges faced beyond bereavement.